Halo nuclei in a three-body model and universal characteristics of low-energy few-body systems - Tomio, Lauro [UNESP]; Yamashita, Marcelo Takeshi [UNESP]; Frederico, T.; Delfino, A. (AIP Publishing, 2010)
Within general characteristics of low-energy few-body systems, we revise some well-known correlations found in nuclear physics, and the properties of low-mass halo nuclei in a three-body neutron-neutron-core model. In this context, near the critical conditions for the occurrence of an Efimov state, we report some results obtained for the neutron- 19C elastic scattering. © 2010 American Institute of Physics.
Keywords: bound-states; Few body systems; halo nuclei; three-body